Pharmacokinetics of Nafcillin in Patients with Renal Failure - Diaz, Carlos R. (1977)
Nafcillin, a pencillinase-resistant penicillin, is frequently used for treatment of staphylococcal infections in hemodialysis patients. Despite its widespread use, there is a paucity of available data regarding the pharmacokinetics of nafcillin in hemodialysis patients. Therefore, sodium nafcillin, 25 mg/kg, was given intravenously over a 5- to 15-min period to 12 hemodialysis patients. Eleven patients were studied during dialysis, and eight of these were studied again during the interdialysis period. The initial serum half-life for nafcillin was 0.208 h during dialyses and 0.278 h between dialyses. The terminal half-life was 1.48 h during dialyses and 1.89 h between dialyses. There was no statistically significant difference between these values. These data indicate that renal failure does not appreciably affect the serum half-life of nafcillin, and hemodialysis does not accelerate the rate of clearance of nafcillin from the blood. Therefore, no modification of the usual nafcillin dosage is necessary when using this drug in hemodialysis patients.